2022
DOI: 10.1021/acsomega.2c03185
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into the Binding of Huperzine a with Human Transferrin: Computational, Spectroscopic and Calorimetric Approaches

Abstract: Huperzine A (HupA), an alkaloid found in the club moss Huperzia Serrata, has been in use for centuries in Chinese traditional medicine to treat dementia owing to its ability to inhibit the cholinergic enzyme acetylcholinesterase (AChE), thus acting as an acetylcholinesterase inhibitor (AChEI). An imbalance of metal ions in the brain is linked to Alzheimer’s disease (AD) pathology. Transferrin (Tf) is a crucial player in iron homeostasis, thus highlighting its significance in AD. This study explores the plausib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Molecular docking molecular dynamics simulation demonstrated HuA could bind with the functionally active region of Tf, providing a direct reason for reducing TBI-depended iron uptake in CNS diseases. 56 In this study, we found that HuA-LIP decreased ferric content and the total iron content, which was superior to solely HuA administration. However, HuA cannot chemically react directly with ferrous and ferric iron ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 51%
“…Molecular docking molecular dynamics simulation demonstrated HuA could bind with the functionally active region of Tf, providing a direct reason for reducing TBI-depended iron uptake in CNS diseases. 56 In this study, we found that HuA-LIP decreased ferric content and the total iron content, which was superior to solely HuA administration. However, HuA cannot chemically react directly with ferrous and ferric iron ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 51%
“…To assess the binding strength between citral and htf, we conducted a fluorescence-based quenching experiment at different temperatures using a Jasco spectrofluorometer (FP-6200). Our analysis followed established protocols from previous studies [ 21 , 42 , 43 ]. In a bid to ensure accuracy, we corrected “inner filter effect”.…”
Section: Methodsmentioning
confidence: 99%